Species indicators for naturally-regenerating and old calcareous grassland in southern England. (June 2019) - Wagner, Markus; Fagan, Kate C.; Jefferson, Richard G.; Marrs, Rob H.; Mortimer, Simon R.; Bullock, James M.; Pywell, Richard F.
Highlights: 30 species were indicative of natural regeneration stages of calcareous grassland. Order of colonization correlated well with an index of establishment limitation. Three groups of indicator species were defined for assessing restoration progress. Species indicators could help identify old grassland and conserve it via AES. Abstract: Habitat restoration requires realistic goals. To naturally regenerate European lowland calcareous grassland, whose extent has severely declined, over a century may be required for vegetation to become indistinguishable from that of old calcareous grassland. Progress of natural regeneration can be characterized using member species of the reference vegetation as indicators of favourable site condition. Chronosequence studies have suggested that calcareous-grassland species differ predictably in their ability to colonize ex-arable land, with some usually colonizing early on, and others in later stages. If such patterns are affected by gradually-attenuating establishment limitation, this would have important implications for restoration practice and indication of progress. Particularly, late-colonizing species might be better indicators of favourable site conditions than early colonizers. To explore these aspects, we have reanalysed chronosequence data previously used to investigate causal mechanisms affecting calcareous-grassland restoration progress. We carried out an indicator species analysis to determine which species are indicative of particular stages of natural regeneration. Using correlation analyses, we tested whether species colonization patterns matched those found by previous chronosequence studies that were geographically more limited or relied on more informal approaches to determine species order of colonization. Correlation analyses were also used to test whether order of colonization could be explained by establishment limitation or by dispersal limitation, or by established plant strategies that underlie such limitations. We identified 30 species as indicative of particular stages of natural regeneration, including nine that specifically indicate old calcareous grassland. Correlation results confirmed high congruence with species order of colonization in previous chronosequence studies, and indicated that establishment limitation plays a role in shaping species order of colonization, potentially mediated through differential stress tolerance. We failed to demonstrate a role of dispersal limitation in shaping order of colonization. Based on our results, we derived three categories of indicator species for passively-restored calcareous grassland, mirroring the regeneration stage during which these species usually colonize. This includes a category labelled by us as 'old-grassland indicators' that achieve notable abundance only in old grassland. We conclude by discussing how such a categorization can benefit the measurement of restoration progress, the tentative identification of old grassland and its conservation, e.g. through linking agri-environment payments to the occurrence of old-grassland indicators, thus fostering positive change in farmer attitudes towards old grassland.